Intra-Racial Microagressions Experienced by the Wife in “The Arrangers of Marriage” by Chimamanda Ngozi Adichie - Asmarani, Ratna (Universitas Negeri Semarang, 2025)
Racism is a slippery practice having many subtle facets and layers. The purpose of this paper is to study the intra-racial microagressions experienced by the wife in the short story entitled “The Arrangers of Marriage” written by Chimamanda Ngozi Adichie. To support the analysis, several concepts are borrowed. Within the broader concept of racism, the focus is on the meaning of racial micro-aggressions which have several levels. The common concept of inter-racial microagressions is adapted into intra-racial microagressions to conform to the topic of discussion. The academic analysis is also supported by a combination of sound methods. Within the frame of feminist criticism, data are gathered and analyzed using the library research method and the qualitative research method. For the literary research method, contextual research method is applied which covers the intrinsic and extrinsic elements. The results indicate that due to the feeling of superiority of the New York African husband, intra-racial microagressions hegemonize the Lagos African wife in the forms of microattacks, microinsults and microinvalidations. The intention of the Lagos African wife to escape from the intra-racial microagressions must be postponed due to her helpless situation at the time being although now she has a female friend who is willing to help her get out of this situation.